The effect of aqueous extract of Morinda lucida on haematological parameters and intestinal ATPases, lactase activity and histopathology studies in lactose induced diarrhea in Wistar rats - Ugbeni C.O. and Idiakheua D.O. (African Journal of Biological Sciences, 2019)
Diarrhea remains a major health burden in developing society till date. Efforts aimed at ameliorating this condition is very imminent. In this study, the antidiarrheal effect of aqueous extracts (dried and fresh forms) of M. lucida leaves was evaluated in Wistar rats. 25% lactose enriched diet was used to induce diarrhea. 25 Wistar rats of an average weight of 150g were divided equally into five groups labeled A-E. The diet was admonished for 72 h to rats in groups B-E. Fresh aqueous extract of M. lucida, dried aqueous extract of M. lucida and loperamide were then administered to groups C-E respectively for the next seven days. The animals were then sacrificed and blood collected for lactase, intestinal ATPases, and some haematological parameters were assayed using standard laboratory procedures. Histopathological examination of the small intestine was also examined. Our results showed a significant increase in the intestinal lactase activity of diarrheic rats. However, the dried extract was able to restore parity with the control. We observed a significant increase in the activities of Na+/K+-ATPase and Mg2+-ATPase while a decrease in the activity of Ca2+ATPase in lactose induced diarrheic rats when compared with the control. The extracts of M. lucida further increased significantly the activity of Na+/K+-ATPase and Mg2+-ATPase when compared with the control and the untreated group. However, no significant effect of the extracts on Ca2+ATPase was observed. On haematological parameters, we observed increase in hematocrit and hemoglobin. Treatment with fresh extract and loperamide was able to reverse this increase. Furthermore results of the differential white blood cell count revealed higher lymphocyte count in the group given dried extract of M. lucida. The extracts were able to ameliorate the aberrations observed in the architecture of the intestinal lumen.
Keywords: Morinda lucida, Aqueous extracts, Lactose, Wistar rats, Diarrhea.